Unique destination attributes as a basis of tourism experience - Zabukovec Baruca, Petra (Academica turistica, 2022)
In today’s highly competitive tourism market, tourists are not only interested in new, unique tourism products and services, but also in unique tourism experiences, as experiences represent an important competitive advantage for a destination. Therefore, the aim of this paper is to explore the attributes of a destination’s identity that are defined as unique, by analysing unique experiences in three main coastal destinations in Slovenian Istria and defining communication strategies to promote the uniqueness of their tourism experiences. The results of a qualitative research confirm that the uniqueness of tourism experiences results from the attributes of the destination’s identity. These attributes primarily relate to nature and natural resources, cultural heritage, and culinary experiences. The unique tourism experiences are conveyed through speciality, innovation, authenticity and various positive emotions such as hedonism, excitement, curiosity, surprise, happiness, and pleasure to ensure memorable value-added experiences and encourage tourists to visit year-round. The study contributes to the knowledge of unique tourism experiences. Finally, theoretical implications, limitations, and recommendations for future research are provided.In today’s highly competitive tourism market, tourists are not only interested in new, unique tourism products and services, but also in unique tourism experiences, as experiences represent an important competitive advantage for a destination. Therefore, the aim of this paper is to explore the attributes of a destination’s identity that are defined as unique, by analysing unique experiences in three main coastal destinations in Slovenian Istria and defining communication strategies to promote the uniqueness of their tourism experiences. The results of a qualitative research confirm that the uniqueness of tourism experiences results from the attributes of the destination’s identity. These attributes primarily relate to nature and natural resources, cultural heritage, and culinary experiences. The unique tourism experiences are conveyed through speciality, innovation, authenticity and various positive emotions such as hedonism, excitement, curiosity, surprise, happiness, and pleasure to ensure memorable value-added experiences and encourage tourists to visit year-round. The study contributes to the knowledge of unique tourism experiences. Finally, theoretical implications, limitations, and recommendations for future research are provided.
Keywords: destination; doživetja; edinstvenost; tourism experience; turistične destinacije; turizem; unique attributes; uniqueness